Operational status of export-oriented RMG factories during Covid-19 pandemic: a rapid survey conducted by the ‘Mapped in Bangladesh’ project - Shajahan, Sadril; Islam, MD. Faizul; Chowdhury, Fahim S; Kaium, Md. Abdullah Al; Ahmad, Faria (Mapped in Bangladesh (MiB) Project, Centre for Entrepreneurship Development (CED), Brac University, 2021)
This study is part of Phase 1 Rapid Survey of the Mapped in Bangladesh (MiB) project, with bthe objective to identify to what extent the factories in the 3 districts are operational and producing face masks and PPEs (personal protective equipment) along with or without their regular products during the current pandemic. Additionally, the survey intended to collect relevant information, such as: the current number of workers at these factories, total capacity currently utilized in these operational factories, and to what extent these factories are expecting to resume their regular operation from June 202 if the Covid-19 pandemic crisis continues. The research was conducted through phone survey since the project collected contact information of factory management as a part of main data points during MiB’s census. According to the findings, 1686 factories who responded to the survey, 1080 factories were operational during the survey period (2-7 May 2020) among which only 14% of the factories said that they were producing PPEs and/or face masks along with their regular products while 86% operational factories were engaged in producing regular products. The survey also revealed that majority of the factories (801) in all districts were running with or below 60% of their capacity.